COMPREHENDING READING THROUGH CLOZE PROCEDURE TO YEAR-11 STUDENTS OF SMA 1 MERAKAI - Cenderato , S.Pd, M.Pd (Universitas Kapuas, 2017)
This research was conducted to answer the research question: “Is the use of cloze procedure effective to test reading comprehension of the eleventh grade students of SMUN 1 Nanga Merakai in academic year 2015/2016?”The method of this research was a Pre-experimental Study with Pretest,the treatment and Posttest. The population of this research was the students of The Eleventh Grade Students of SMAN 1 Nanga Merakai in Academic Year 2015/2016. The population was 40 students of class XI IPA and it was also considered as a total sample .The technique of data collecting was matching test. The students tried to find the deleted words from texts. The research findings showed the total score of pretest is 2735 with the mean score 68.375 and categorized “Average”.Furthermore, the result of posttest is 3155 with the mean score 78.875 and categorized “Good”. The result of computation on the t-test with 7,56 is higher than the t-table for the degree of freedom N-1 (40-1)=39 is 2.042. Moreover, the computation on Effect Size of the treatment is 1.13. It is categorized “Highly Effective” because the result of 1.13 is higher than 0.8 that is the high level of effectiveness on Effect Size criteia proposed by Burn (ES >0.8 = 1.13>0.8). From the computation, it can be concluded that the teaching reading comprehension by using Cloze Procedure is “highly effective”.